MEDAN GAYA BERAT PADA BATUAN OFIOLIT (ULTRAMAFIK) DI BEOGA, PAPUA DAN IMPLIKASI TERHADAP GENESIS ALIH TEMPATNYA - Budi Setyanta; Bambang Suci Widijono (Jurnal Geologi dan Sumberdaya Mineral, 2009)
In Beoga, Puncak Jaya, Papua, a group of ultramafic rocks consisting of piroxenite, dunite, serpentenite and peridotite are exposed. The distribution of these rocks are very large, lying alongside east - west direction, reaching 50 km and 100 km long. The gravity fields in this region exhibit an elliptic gravity anomaly pattern ranging from -25 to 160 mGals. The gravity modelling and geological analysis suggest that ophiolite has been fragmented and exposed due to obduction, caused by an interaction between Pacific oceanic and Australian granitic plates. This tectonic setting may cause Mulia and its surrounding area to be susceptible to geological hazards such as earthquake and landslides.Â Keywords : gravity potentials, ophiolite, genesis, geology potential